ANALYZING THE CONDITION OF THE CURRENT SYSTEM OF OPPOSING PROFIT LEGALIZATION IN NON-CREDIT FINANCE ORGANIZATIONS - Nadezhda M. Chuikova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article analyzes the key problematic zones in the national system of finance monitoring which is based on the combination of institutional bodies and finance organizations. Among all entities of the primary finance monitoring the sector of non-credit finance organizations was singled out, which in the current situation is more vulnerable to the risk of being involved in dubious clients' operations. By analyzing the legal field of the Russian Federation it was found out that the definition of 'non-credit organization' is not available. The author explains the essence of this type of finance organization. The use of new norms of anti-legalizational legislation is demonstrated, their impact on finance market is depicted.